**Question:**

find a/b+b/a =-1

__3ab__

a^2+b^2/ab=-1

a^2+b^2=-ab

(a-b)(a^2+b^2+ab)

now substitute the value

(a-b)(-ab+ab)

(a-b)(0)

0 ans

__-1__

0

0

{° ¡ °}

~

| |

/ [ ] \

| \ |

°•

°•

°•

kal batata __hu__

Just chill bro khud kar __lega__

This is absurd asx+1/x never equals -1 for any real __x__

=> (a^2 + b^2)/ab = -1

=> a^2 + b^2 = -ab

=> a^2 + ab + b^2 = 0

=> (a-b)(a^2 + ab + b^2) = 0(a-b)

=> a^3 - b^3 = 0

=> a^3 = b^3

=> a = b

With the given equation, we can get only this solution:

a=b

If any numerical value is needed then we need another equation as there are 2 variables.